Social Media Marketing as a Key Determinant of Brand Gestalt and Brand Personality - Edwina Fabiola Rayo; Natashia Merrylien Rayo; Deske W. Mandagi (Penerbit Goodwood, 2024)
Purpose: This study aims to explore the relationship between social media marketing (SMM), brand personality, and brand gestalt, with a particular focus on the mediating role of brand gestalt among.Methodology: The research was conducted among 232 customers of Starbucks Indonesia, utilizing a quantitative descriptive approach. The Structural Equation Modelling (SEM) method was employed, with data analysis carried out using the SmartPLS statistical program.Results: The study found that SMM has a positive and significant impact on the dimensions of brand gestalt, namely story, sensescape, servicescape, and stakeholders. These dimensions, in turn, significantly influence brand personality. Additionally, the brand gestalt dimensions fully mediate the relationship between SMM and brand personality.Conclusions: This study aims to examine the impact of social media marketing on brand personality, with brand gestalt serving as a mediating variable, focusing on Starbucks consumers in Indonesia.Limitations: The study is limited by its focus on Starbucks Indonesia customers, which may affect the generalizability of the findings to other brands or regions.Contribution: The study is one of the first empirical works to integrate social media marketing, brand personality, and brand gestalt. It offers valuable insights for practitioners on how to effectively leverage SMM and brand gestalt to shape brand personality.